Membrane fusion and the lamellar-to-inverted-hexagonal phase transition in cardiolipin vesicle systems induced by divalent cations. - Ortiz, A (1999)
The polymorphic phase behavior of bovine heart cardiolipin (CL) in the presence of different divalent cations and the kinetics of CL vesicle fusion induced by these cations have been investigated. (31)P-NMR measurements of equilibrium cation-CL complexes showed the lamellar-to-hexagonal (L(alpha)-H(II)) transition temperature (T(H)) to be 20-25 degrees C for the Sr(2+) and Ba(2+) complexes, whereas in the presence of Ca(2+) or Mg(2+) the T(H) was below 0 degrees C. In the presence of Sr(2+) or Ba(2+), CL large unilamellar vesicles (LUVs) (0.1 microm diameter) showed kinetics of destabilization, as assessed by determination of the release of an aqueous fluorescent dye, which strongly correlated with the L(alpha)-H(II) transition of the final complex: at temperatures above the T(H), fast and extensive leakage, mediated by vesicle-vesicle contact, was observed. On the other hand, mixing of vesicle contents was limited and of a highly transient nature. A different behavior was observed with Ca(2+) or Mg(2+): in the temperature range of 0-50 degrees C, where the H(II) configuration is the thermodynamically favored phase, relatively nonleaky fusion of the vesicles occurred. Furthermore, with increasing temperature the rate and extent of leakage decreased, with a concomitant increase in fusion. Fluorescence measurements, involving incorporation of N-NBD-phosphatidylethanolamine in the vesicle bilayer, demonstrated a relative delay in the L(alpha)-H(II) phase transition of the CL vesicle system in the presence of Ca(2+). Freeze-fracture electron microscopy of CL LUV interaction products revealed the exclusive formation of H(II) tubes in the case of Sr(2+), whereas with Ca(2+) large fused vesicles next to H(II) tubes were seen. The extent of binding of Ca(2+) to CL in the lamellar phase, saturating at a binding ratio of 0.35 Ca(2+) per CL, was close to that observed for Sr(2+) and Ba(2+). It is concluded that CL LUVs in the presence of Ca(2+) undergo a transition that favors nonleaky fusion of the vesicles over rapid collapse into H(II) structures, despite the fact that the equilibrium Ca(2+)-CL complex is in the H(II) phase. On the other hand, in the presence of Sr(2+) or Ba(2+) at temperatures above the T(H) of the respective cation-CL complexes, CL LUVs rapidly convert to H(II) structures with a concomitant loss of vesicular integrity. This suggests that the nature of the final cation-lipid complex does not primarily determine whether CL vesicles exposed to the cation will initially undergo a nonleaky fusion event or collapse into nonvesicular structures.